Sustainability Reports as a Legitimacy Tool: A Qualitative Perspective from Financial Accounting Practices - Hasiah; Hatta, Harmiati; Mide, Nuraisyah Zain (Universitas Pendidikan Ganesha, 2025)
Although the number of sustainability reports in Indonesia has increased—particularly after the enactment of the Financial Services Authority’s Regulation No. 51/POJK.03/2017—the substance, honesty, and motivations behind these reports remain questionable. This study explores sustainability report practices as a means of organizational legitimacy within financial accounting. Using an interpretive, qualitative approach with a single-case study design, the research explores the subjective experiences of six key informants directly involved in preparing sustainability reports at a publicly listed company in Indonesia. The findings indicate that sustainability reports are employed to comply with regulatory obligations and market demands and serve as a symbolic communication tool and strategic representation of the company. Selective disclosure is not merely technical but also carries political and social significance because it is used to build organizational legitimacy. In this case study, selective disclosure is evident in how companies emphasize achievements that align with the Sustainable Development Agenda, such as carbon emission reduction programs, social responsibility activities in the community, and environmentally friendly innovations. In contrast, sensitive issues such as program failures, negative operational impacts on the environment, or dissatisfaction among some community members tend to be minimized or even omitted from the narrative. Selective disclosure of information that supports a positive corporate image and the construction of sustainability narratives aligned with managerial interests. This study reinforces the relevance of legitimacy theory and sociological approaches in understanding accounting reporting, revealing that sustainability reports constitute a discursive arena in which the meaning of sustainability is socially and politically constructed.